2022
DOI: 10.3892/etm.2022.11316
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory activity of soybean hull polysaccharide on macrophages

Abstract: Water-soluble polysaccharide isolated from soybean hull and fractionated using ion-exchange chromatography were investigated to determine their molecular characteristics and immunostimulating activity. In the present study, soybean hull polysaccharide (SHP) was separated and purified to obtain three main fractions (F1, F2 and F3), and their chemical and monosaccharide compositions were analyzed. SHP was mainly composed of carbohydrates (64.3%), proteins (16.2%) and sulfates (12.5%), with minor levels of uronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Gel permeation chromatography (Sephadex-G series and Sephacryl-S series) separates polysaccharides based on molecular weight differences ( 27 , 31 , 33 ). For example, Wang et al ( 6 ) used different concentrations of NaCl to separate three different polysaccharides (F1, F2, F3) by DEAE Sepharose Fast Flow. Hu et al ( 34 ) used DEAE-Cellulose to separate neutral polysaccharides (SSPS-N) and acidic polysaccharides (SSPS-A) from Okara.…”
Section: Extraction Isolation and Purification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gel permeation chromatography (Sephadex-G series and Sephacryl-S series) separates polysaccharides based on molecular weight differences ( 27 , 31 , 33 ). For example, Wang et al ( 6 ) used different concentrations of NaCl to separate three different polysaccharides (F1, F2, F3) by DEAE Sepharose Fast Flow. Hu et al ( 34 ) used DEAE-Cellulose to separate neutral polysaccharides (SSPS-N) and acidic polysaccharides (SSPS-A) from Okara.…”
Section: Extraction Isolation and Purification Methodsmentioning
confidence: 99%
“…Wang et al ( 6 ) investigated the immune activity of soybean chitin polysaccharide (SHP) on macrophages. The study found that SHP can promote the proliferation of RAW 264.7 cells, produce NO, IL-6, TNF-α, which was specifically recognized by Toll-like receptor 2, and then up-regulate the expression levels of mitogen-activated protein kinase and nuclear factor κB pathway downstream proteins.…”
Section: Biological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Legumes were reported to reduce the prevalence of various diseases. [4,5] Its polyphenol content, which has significant antioxidant activity, accounts for its therapeutic properties. [6,3] Vicia faba (gen. Vicia, fam.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to medicinal plants, legumes are dietary ingredients with strong biological activity, and they represent a primary source of sustenance for humans. Legumes were reported to reduce the prevalence of various diseases [4,5] . Its polyphenol content, which has significant antioxidant activity, accounts for its therapeutic properties [6,3] …”
Section: Introductionmentioning
confidence: 99%